Efficacy of respiratory physiotherapy preceding to heart surgery with extracorporeal circulation - Eloy Rueda-Gomariz; Carlos A. Castillo-Sarmiento; José Ramón Muñoz-Rodríguez; Inmaculada Ballesteros-Yánez (Cirugía Cardiovascular)
Introduction and objectives: Heart surgery is one of the most important tools for the treatment of cardiovascular diseases. Postoperative pulmonary complications in patients undergoing heart surgery represent a meaningful clinical problem.Respiratory physiotherapy is essential in the management of patients during postoperative period, contributing to a better prognosis.Our objective is to evaluate the efficacy of respiratory physiotherapy prior to cardiac surgery in reducing postoperative complications and hospital stay. Methods: Randomized, controlled and observational study. A group of 92 patients who underwent heart surgery with extracorporeal circulation were analyzed in the Hospital Puerta del Mar (Spain), divided into 2 groups (control group and experimental group with previous respiratory physiotherapy). We study different postoperative complications and hospital stay. Results: Atelectasis, pleural effusion, and sternal dehiscence were altered between both groups. An improvement in the intubation time and the reintubation rate was reported in the experimental group, in addition, lower oxygen consumption, an improvement in the fulfillment of respiratory physiotherapy following surgery and a shorter overall hospital stay and in the post-operative care unit was also observed. Conclusion: Fulfillment of respiratory physiotherapy preceding to heart surgery decreases pulmonary complications and hospital stay, as well as accelerates the recovery of the breathing capacity. Resumen: Introducción y objetivos: La cirugía cardiaca es una de las herramientas más importantes para el tratamiento de las enfermedades cardiovasculares. Las complicaciones pulmonares posoperatorias en pacientes sometidos a cirugía cardiaca representan un problema clínico significativo.La fisioterapia respiratoria es esencial en el manejo de los pacientes durante el posoperatorio, contribuyendo a un mejor pronóstico.Nuestro objetivo es evaluar la eficacia de la fisioterapia respiratoria previa a la cirugía cardiaca en la reducción de las complicaciones posoperatorias y la estancia hospitalaria. Métodos: Estudio aleatorizado, controlado y observacional. Se analizó un grupo de 92 pacientes sometidos a cirugía cardiaca con circulación extracorpórea en el Hospital Puerta del Mar (España), divididos en dos grupos (grupo control y experimental con fisioterapia respiratoria previa). Estudiamos diferentes complicaciones posoperatorias y estancia hospitalaria. Resultados: La atelectasia, el derrame pleural y la dehiscencia esternal se alteraron entre ambos grupos. Se observó una mejora en el tiempo de intubación y en la tasa de reintubación en el grupo experimental, además de un menor consumo de oxígeno, una mejora en el cumplimiento de la fisioterapia respiratoria tras la cirugía y una estancia hospitalaria global y en la unidad de cuidados posoperatorios más corta. Conclusión: El cumplimiento de la fisioterapia respiratoria previa a la cirugía cardiaca disminuye las complicaciones pulmonares y la estancia hospitalaria, asimismo, acelera la recuperación de la capacidad respiratoria.